2019
DOI: 10.3390/ijerph16081439
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Cu-Mn-Ce@γ-Al2O3 to Catalyze Ozonation in Coal Chemical Wastewater-Biotreated Effluent

Abstract: Cu-Mn-Ce@γ-Al2O3 was prepared by incipient wetness impregnation and used to catalyze ozonation in a coal chemical wastewater-biotreated effluent. The preparation factors that considerably affected the catalytic performance of Cu-Mn-Ce@γ-Al2O3, specifically metal oxide loading percentage, calcination temperature, and calcination time, were examined. The catalyst was characterized by scanning electron microscopy, energy dispersive spectrometry, X-ray diffraction, and Brunauer-Emmett-Teller analysis. The optimal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Namely, O 3 as an oxidant, reacts with sulfur directly and rapidly with acidic conditions. While, O 3 is induced by the hydroxide ions in alkaline conditions to produce hydroxyl free radicals and other active radical [26] , [27] . The decomposition of O 3 in the alkaline system produces a series of chain reactions and active radical formation reactions, as shown in Eqs.…”
Section: Resultsmentioning
confidence: 99%
“…Namely, O 3 as an oxidant, reacts with sulfur directly and rapidly with acidic conditions. While, O 3 is induced by the hydroxide ions in alkaline conditions to produce hydroxyl free radicals and other active radical [26] , [27] . The decomposition of O 3 in the alkaline system produces a series of chain reactions and active radical formation reactions, as shown in Eqs.…”
Section: Resultsmentioning
confidence: 99%
“…The heterogeneous catalytic ozonation uses solid catalysts (e.g., metal oxides and metals on supports). There are two ways for O 3 to be decomposed in this system: at the catalyst surface and/or react with organics adsorbed on the catalyst surface to produce HO • [41][42][43]. Many noble metals and metal oxides, immobilized or not on supports, have been used for heterogeneous catalytic ozonation [44,45], being the order of catalytic activity for the decomposition of ozone following one [46]:…”
Section: •àmentioning
confidence: 99%
“…To further improve the catalytic effect, γ-Al 2 O 3 has been used as a carrier to load some metal oxides, and its catalytic effect on ozone has been studied [ 11 , 12 ]. Among these, the active components generally include transition metals [ 13 ], precious metals [ 14 ], rare earth elements [ 15 ], and some metal oxides [ 16 ]. Certain precious metals have been shown to have the best effect, but it has also been found that the transition metals (Mn, Fe, Cu and Zn) [ 17 ], although not producing the best effect, still produce a good effect compared with many other metals, and transition metals are easily obtained [ 18 ].…”
Section: Introductionmentioning
confidence: 99%